Crystallization process, microstructure, thermal behavior, and magnetic properties of melt‑spun Fe86Cr6P6C2 ribbons - L. Abadlia; M. I. Daoudi; S. Alleg (Applied Physics A (2023) 129:487 https://doi.org/10.1007/s00339-023-06745-4, 2023)
The crystallization process, microstructure, thermal stability, and magnetic properties of Fe86Cr6P6C2 amorphous ribbons were studied by X-ray difraction, scanning electron microscopy coupled with energy dispersive X-ray spectroscopy, differential scanning calorimetry, and vibration sample magnetometry. The crystallization process occurs in three stages where nanocrystalline α-Fe solid solution, Fe3P phosphide, θ-Fe3C and ε-Fe3C carbides are formed. The crystallite size increases with increasing annealing temperature and remains at the nanometer scale (20–88 nm). The microstructure of the annealed ribbons consists of lamella, fne platelets, alternate planes of ferrite and cementite, and grains with diferent shapes and sizes. The activation energies (499, 386, and 369 kJ/mol) are determined by Kissinger method. The melt-spun ribbons exhibit a low coercivity of 16.598 Oe and a high saturation magnetization of 0.635 emu compared to the annealed ones. The saturation magnetization decreases to a minimum value for the annealed ribbons at 758 K and then increases with increasing the annealing temperature. The Curie temperature increases from 447.4 K for the melt-spun ribbons to 638 K for the fully crystallized ribbons due to the development of the α-Fe phase.
Keywords: Fe–Cr–P–C alloys · XRD · Thermal stability · Crystallization kinetics · Magnetic properties